Awaken The Giant Within : How To Take Immediate Control Of Your Mental,Emotional, Physical & Financial Destiny - Robbins, Anthony (Rawalpindi Services Book Club, 2014)
Author shows how to take immediate control of mental, emotional, physical, and financial destiny with strategies from his Date with Destiny seminar.
Keywords: Awaken The Giant Within : How To Take Immediate Control Of Your Mental,Emotional, Physical & Financial Destiny -- Psychology -- Success--Psychological aspects -- Control (Psychology)